Optimizing neonatal care: streamlined positive blood culture reporting via laboratory automation with BacT/ALERT 3D - U. A., Premjith Lal; Mantri, Rupali S.; Ambhore, Nitin A.; Raut, Sharmila S. (International Journal of Research in Medical Sciences, 2026)
Background: Sepsis presents a potentially life-threatening medical condition marked by a systemic inflammatory response throughout the body, triggered by various pathogenic organisms found in the bloodstream. Neonatal sepsis stands as the third primary contributor to neonatal mortality. Blood culture methods have evolved significantly from conventional techniques involving bottles of nutrient broths cultured in incubator and subsequent subculture based on visual assessments to modern automated systems. These automated instruments, which are continuously monitored and enhanced the efficiency of blood cultures. One of the widely employed blood culture systems in numerous diagnostic microbiology laboratories is the BacT/ALERT 3D system developed by BioMérieux Inc. Methods: This is a hospital-based observational study we were trying to evaluate the time to positivity (TTP), identification and antimicrobial susceptibility patterns of causative organism in blood culture. One thirty-nine matched pairs of blood cultures from neonates were evaluated by the BacT/ALERT 3D system. Results: Out of 139 blood samples that were processed 40 (28.77%) were positive. The median time to detection in the BacT/ALERT 3D system for isolates was found to be on an average of 11.8 hours in our study. Gram-negative isolates were found most common cause of sepsis, accounting for 75%, compared to gram-positive isolates, which accounted for 25%. Among the identified isolates, Klebsiella pneumoniae and Escherichia coli were the most prevalent, responsible for 25% each. Conclusions: Neonatal septicemia poses a life-threatening emergency. The BacT/ALERT 3D system is more sensitive, rapid, higher efficiency in detecting prevalent bloodstream pathogens.